Amyotrophic lateral sclerosis-associated mutant profilin 1 increases dendritic arborisation and spine formation in primary hippocampal neurons. (16th November 2015) - Brettle, Merryn; Suchowerska, Alexandra K.; Chua, Sook W.; Ittner, Lars M.; Fath, Thomas
Highlights: Mutant PFN C71G expression in cultured hippocampal neurons promotes dendrite extension and branching. PFN C71G increases dendritic spine density in cultured hippocampal neurons. PFN C71G forms cytoplasmic inclusions in hippocampal neurons. Abstract: Amyotrophic lateral sclerosis (ALS) is the most common motor neuron disease and familial ALS accounts for 10% of cases. The identification of familial ALS mutations in the actin-binding protein profilin 1 directly implicates actin dynamics and regulation in the pathogenesis of ALS. The mechanism by which these mutations cause ALS is unknown. In this study we show that expression of the ALS-associated actin-binding deficient mutant of PFN1 (PFN1 C71G ) results in increased dendritic arborisation and spine formation, and cytoplasmic inclusions in cultured mouse hippocampal neurons.